Deixis and References in The Alice in Wonderland Movie - Ida Ayu Komang Pradnya Paramita; I Gusti Agung Istri Aryani; Galuh Febri Putra (Badan Penerbit STIEPARI Press, 2025)
This study, entitled “Deixis and References in the Alice in Wonderland Movie,” aims to identify various types of deixis and analyze the reference of the meaning of each type of deixis used in the movie Alice in Wonderland. The data source was obtained from the Alice in Wonderland movie, an American fantasy film directed by Tim Burton and produced by Walt Disney Pictures, released on February 25, 2010, based on a screenplay by Linda Woolverton. This study uses a qualitative method with documentation and observation techniques. The data was taken from Scripts.com and completed with repeated movie viewing. The steps include downloading the script, watching the movie, identifying utterances containing deixis, and analyzing them according to Levinson’s (1983) deixis theory and Cruse’s (2006) reference theory. The analysis is presented using informal descriptive methods. The results of this study indicated that five types of deixis were employed in the movie: person deixis, place deixis, temporal deixis, discourse deixis, and social deixis. The movie Alice in Wonderland (2010) data represented each type of deixis. The analysis revealed that each deixis category appeared with varying frequency: 334 instances of personal deixis, 35 instances of place deixis, 27 instances of time deixis, 87 instances of discourse deixis, and 41 instances of social deixis. These findings suggest that personal deixis was the dominant type used by the characters in the movie, emphasizing the role of speaker-hearer reference in the narrative discourse. Furthermore, two kinds of reference were found, anaphora and cataphora.